OVERPRODUCTION OF STREPTOKINASE FROM STREPTOCOCCUS MUTANS EBL-37-UV90 BY PERFORMING OPTIMIZATIONAL STUDIES - G. Akbar1; M. A. Zia; A. Jamil; F. A. Joyia (Journal of Animal and Plant Sciences, 2021)
Beta-hemolytic Streptococci are being used to produce streptokinase (SK) for decades however, increase in production rate is lucrative. The focus of this study was to enhance the production of SK from mutant derived strain Streptococcus mutants EBL-37-UV90. Fermentation parameters were studied by response surface methodology (RSM) like pH (5-8), fermentation time (12-60 hours), temperature (22-66°C) and inoculum size (1-5) in the presence of carbon source (glucose 1%), yeast extract (3.5%) and corn steep liquor (4%). Model was statistically analyzed by ANOVA using RSM (design expert version 7.0) and coefficient with P≤0.05 was taken as significant. Statistical examination on response surface and contour plot was carried out the effects of single factor and interaction between two factors. Streptokinase was purified by standard methodologies such as ammonium sulphate, salting out process, dialysis, ion exchange and size exclusion chromatography. The maximum streptokinase production was obtained with the mutual interaction of different optimization parameters at 37°C temperature, 36 hours fermentation time, 6.5 pH and 3.0 ml inoculum size. Results indicated that mutant Streptococcus mutans EBL-37-UV90 exhibited the highest production of SK with enzyme activity 275.6 U/mL which is 4.6-fold higher yield than control. Moreover, after purification processes 2.6 folds enzyme activity has been decreased and 75.66 folds specific activity has been increased as compared to crude enzyme. An amount of 38.09% streptokinase was recovered in purified form as compared to crude extract. The present study is a step forward towards cost effective production of streptokinase by virtue of enhanced activity per unit of the purified enzyme which may have important application in treatment of cardiovascular diseases.
Keywords: Mutagenesis; Purification; RSM; Streptokinase; Streptococcus mutans EBL-37-UV90